2018
DOI: 10.1111/jgh.14517
|View full text |Cite
|
Sign up to set email alerts
|

Risk of colorectal cancer for fecal immunochemistry test‐positive, average‐risk patients after a colonoscopy

Abstract: Background and Aim Because the risk of colorectal cancer has not been well examined in fecal immunochemistry test (FIT)‐positive patients who previously underwent colonoscopy, this study aimed to investigate this topic. Methods This was a single‐center, observational study of prospectively collected data in Japan. FIT‐positive, average‐risk patients who underwent colonoscopy were divided into groups as follows: those who never underwent colonoscopy in the past (no colonoscopy group), those with a history of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…A study found that the incidence and mortality of colon cancer have gradually increased in recent years (Bray et al, 2018). The current diagnostic strategies for colon cancer mainly include biopsy, laboratory examination, and colonoscopy (Cross et al, 2019;Kawamura et al, 2019). Therefore, establishing a reliable risk assessment model is urgently needed to assess the survival prognosis of patients with colon cancer and optimize clinical treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…A study found that the incidence and mortality of colon cancer have gradually increased in recent years (Bray et al, 2018). The current diagnostic strategies for colon cancer mainly include biopsy, laboratory examination, and colonoscopy (Cross et al, 2019;Kawamura et al, 2019). Therefore, establishing a reliable risk assessment model is urgently needed to assess the survival prognosis of patients with colon cancer and optimize clinical treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…1 We studied the clinical application of a new type of laser thermoablation: the mixed thulium-herbium laser. 2,3 On the basis of previous success on animal models, 3 we compared thulium laser coagulation (TLC) and argon plasma coagulation (APC), and we enrolled 11 patients (7 female, 4 male, mean age 83 years) in the TLC group and 10 patients (6 female, 4 male, mean age 85 years) in the APC group. All patients were receiving antiplatelet/ anticoagulant therapy.…”
Section: Thulium Laser Coagulation: a New Effective Endotherapy To Trmentioning
confidence: 99%
“…In Japan, repeating annual FIT is often performed according to the recommendations of the Ministry of Health, Labour and Welfare, even 1 year after negative colonoscopy. Nevertheless, we have reported the risk of CRC or advanced neoplasia (defined as any tubular adenoma measuring ≥10 mm or with features of villous histology, high‐grade dysplasia, or invasive cancer) to be low in FIT‐positive, average‐risk patients subjected to colonoscopy within 5 years in our Japanese hospital . According to the European Society of Gastrointestinal Endoscopy guidelines, if there is no high‐risk lesion in colonoscopy, rescreening with FIT or colonoscopy is recommended after 10 years .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we have reported the risk of CRC or advanced neoplasia (defined as any tubular adenoma measuring ≥10 mm or with features of villous histology, high-grade dysplasia, or invasive cancer) to be low in FIT-positive, averagerisk patients subjected to colonoscopy within 5 years in our Japanese hospital. 11 According to the European Society of Gastrointestinal Endoscopy guidelines, if there is no high-risk lesion in colonoscopy, rescreening with FIT or colonoscopy is recommended after 10 years. 12 Furthermore, it is not recommended to repeat FIT within 10 years; however, if the FIT is found to be positive within 10 years unexpectedly, it is up to the clinician to decide whether to repeat the colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation